The impact of intercollegiate athletics in higher education (Higher Education Politics and Economics, 2016)
The place of athletics in American higher education has been defended and criticized for well over one hundred years (Camp, 1893). Having become such a popular cultural attraction and tradition, as well as a potential method of generating revenue, the role of college athletics has broadened beyond a student-oriented activity. This article reviews the different ways intercollegiate athletics influences the reputation, operation, and quality of higher education.